Physiological assesment of hunger in female broiler breeders - Najafi, Pardis; Idrus, Zulkifli; M., Husna; Amir, Anna Aryani; Kumari, S.; Soleimani, A. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
The aim of current experiment was to investigate several physiological indicators of stress (corticosterone, heat shock protein, acute phase proteins and serotonin) in broiler breeders subjected to feed restriction. The birds were subjected to five different levels of feed restriction and ad libitum feeding as control group from 28 to 42 days of age. There was a linear increase in serum levels of corticostrone with severity of feed restriction. Only severe levels of feed restriction significantly increased heat shock protein 70 expression in the brain and plasma serotonin concentration. Feed restriction had negligible effect on serum levels of alpha-1 acid glycoprotein, ceruloplasmin and ovotranferrin.